Enhancement of Functional Properties of Liquid Electrolytes for Lithium‐Ion Batteries by Addition of Pyrrolidinium‐Based Ionic Liquids with Long Alkyl‐Chains. Issue 10 (27th May 2020) - Celeste, Arcangelo; Silvestri, Laura; Agostini, Marco; Sadd, Matthew; Palumbo, Stefano; Panda, Jaya Kumar; Matic, Aleksandar; Pellegrini, Vittorio; Brutti, Sergio
Abstract: Three ionic liquid belonging to the N ‐alkyl‐ N ‐methylpyrrolidinium bis(trifluoromethanesulfonyl) imides (Pyr1, n TFSI with n =4, 5, 8) have been added as co‐solvent to two commonly used electrolytes for Li‐ion cells: (a) 1 M lithium hexafluorophosphate (LiPF6 ) in a mixture of ethylene carbonate (EC) and linear like dimethyl carbonate (DMC) in 1 : 1 v/v and (b) 1 M lithium bis‐(trifluoromethanesulfonyl)imide (LiTFSI) in EC : DMC 1 : 1 v/v. These electrolyte formulations (classified as P and T series containing LiPF6 or LiTFSI salts, respectively) have been analyzed by comparing ionic conductivities, transport numbers, viscosities, electrochemical stability as well as vibrational properties. In the case of the Pyr1, 5 TFSI and Pyr1, 8 TFSI blended formulations, this is the first ever reported detailed study of their functional properties in Li‐ion cells electrolytes. Overall, P‐electrolytes demonstrate enhanced properties compared to the T‐ones. Among the various P electrolytes those containing Pyr1, 4 TFSI and Pyr1, 5 TFSI limit the accumulation of irreversible capacity upon cycling with satisfactory performance in lithium cells. Abstract : The pursuit of electrolytes : Innovative non‐aqueous electrolytes for Li‐ion batteries with superior safety features compared to commercial products are formulated and characterized: here, the unique physico‐chemical properties of ionic liquids to push the capability of liquid electrolytes beyond the state‐of‐the‐art are exploited.